Brincadeira e ludicidade na educação infantil: concepções e práticas docentes na rede municipal de Fortaleza - Sousa, Janaína Paula de (2025)
The research deals with play and playfulness in early childhood education, in a study carried out in the city of Fortaleza. Its general objective is to investigate the concepts of play and playfulness throughout the training process of teachers in the municipal network of Fortaleza. From this perspective, it was also proposed to understand the conceptions of playfulness of Kindergarten V teachers, to identify playfulness practices in this context and to analyze the contributions of continuing education, from the teachers' perspective, for the development of a playfulness praxis, configuring specific objectives. To support the theoretical categories present in the research (play, playfulness, training and early childhood education) we rely on the studies of: Ariès (2022); Abramowick and Tebet (2019); Benjamin (2002); Rinaldi (2020); Kohan (2019); Hoyelos (2019); Ostetto (2012); Larrosa (2018); Freire (1997, 2022); Oliveira-Formozinho (2008); Tardif (2014); Imbernón (2010, 2011); Nóvoa (2002); Huizinga (2019); Fochi (2016); Luckesi (2022); Vygotsky (1991, 2001, 2018) among others. Current legislation is also presented as legal support for research discussions. Such studies enabled us to understand the theoretical assumptions of these respective categories. The methodological path was based on qualitative research and a historical-dialectic approach. We carried out field research in an Early Childhood Education Center in the aforementioned municipality with teachers working in the Kindergarten V room. The construction of data occurred through semi-structured interviews and participant observation, with records of photographs, filming and field notes. As a result, the research subjects' conceptions about play and playfulness emerged, crossed by the formative processes that constitute us as teaching and learning subjects in a practice that became coherent. Play and playfulness are present in early childhood education. This finding could be seen through the daily actions involved in affection, care and valuable interactions, creating a context of appreciation for children's cultures, multiple experiences and learning, although we have challenges to be overcome. The theme of play and playfulness is characterized by knowledge that constitutes teaching professionalism, and reflecting on this theme and its impacts is useful for enhancing learning in early childhood education, as well as our professional development, which, in addition to being technical, is sensitive and playful.